Factors Affecting Laser-Trim Stability of Thick Film Resistors. (1977) - Cote, R. E.; Headley, R. C.; Herman, J. T.; Howe, A.
Abstract : Various factors affecting precision of trim and resistor stability are considered. The influence of machine operating parameters (beam power, pulse frequency and trim speed) on resistor performance are examined and quantified through statistically designed experiments for aQ -switched YAG laser system. Laser kerf quality is examined by scanning electron microscopy and related to kerf isolation resistance measurements. A relatively simple, production oriented, quality control test is proposed for rapid determination of kerf electrical stability. In addition, the effect of cut design and extent of trim on precision and stability are discussed.